Development of an Evaluation Instrument Based on the Educational Game Blooket for the Subject of SKI Phase E: The Development of Islam during the Khulafaur Rashidin Era - ulufiyah, siti nahdatul; Aziz, Su'udin; Khoiriyah, Siti (UIN Mataram, 2024)
In the rapidly advancing era of globalisation, information and communication technology have had a significant impact, including in the field of education. The development of innovative learning media is crucial to enrich the teaching and learning process. Although many schools have provided IT media for education, there are still educators who underutilise these resources, particularly as tools for evaluating students. This research adopts a Research and Development (R&D) approach with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. This study aims to assess the implementation of the educational game Blooket as an evaluation instrument for the subject SKI at MA Miftahul Ulum Sitiaji. The research subjects were the students, and data were collected through interviews, observations, and documentation. Data analysis was conducted using normality tests, reliability tests, and t-tests. The results indicate that the validity of the Blooket website as an educational game-based evaluation instrument is excellent, with validation percentages of 71.2% from subject matter experts, 68.5% from Islamic Religious Education teachers, and 94% from media experts. The students' responses to the instrument were also very positive, with an average percentage of 87%. In conclusion, the educational game-based evaluation instrument Blooket is deemed appropriate and effective for use in the learning process. Abstrak: Dalam era globalisasi yang berkembang pesat ini, teknologi informasi dan komunikasi telah membawa dampak signifikan, termasuk dalam sektor pendidikan. Pengembangan media pembelajaran yang inovatif menjadi penting untuk memperkaya proses belajar mengajar. Meskipun banyak sekolah yang sudah menyediakan media IT untuk pembelajaran, masih terdapat pendidik yang kurang memanfaatkannya, terutama sebagai instrumen evaluasi siswa. Penelitian ini menggunakan pendekatan Research and Development (R&D) dengan model ADDIE, yang mencakup lima tahap: analisis, desain, pengembangan, implementasi, dan evaluasi. Tujuan penelitian ini adalah untuk mengetahui penerapan game edukasi Blooket sebagai instrumen evaluasi pada mata pelajaran SKI di MA Miftahul Ulum Sitiaji. Subjek penelitian adalah peserta didik, dan data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Analisis data dilakukan dengan uji normalitas, reliabilitas, dan t-test. Hasil penelitian menunjukkan bahwa validitas website Blooket sebagai instrumen evaluasi berbasis game edukasi sangat baik, dengan persentase validasi dari ahli materi sebesar 71,2%, 68,5% dari guru Pendidikan Agama Islam, dan 94% dari ahli media. Respon peserta didik terhadap instrumen ini juga sangat positif, dengan rata-rata persentase 87%. Kesimpulannya, instrumen evaluasi berbasis game edukasi Blooket layak dan efektif digunakan dalam proses pembelajaran.